2017
DOI: 10.1016/j.jcps.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intelligence on consumers' responsiveness to a pro‐environmental tax: Evidence from large‐scale data on car acquisitions of male consumers

Abstract: Researchers and policy‐makers are increasingly interested in the effects of pro‐environmental tax incentives on consumer responses. However, it is unknown whether consumers' responsiveness to pro‐environmental taxes depends on cognitive ability. We report a natural experiment study, in which a pro‐environmental tax was introduced in Finland, providing an economic benefit for cars with lower CO2 emissions. We examine 140,000 car acquisitions by male consumers, whose intelligence had been tested by Finnish Defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Some have lamented that people’s dearth of understanding and knowledge—due to lack of exposure to information (Gifford 2011), information overload (Horne 2009; Neumann, Roberts, and Cauvin 2012), and confusion (Chen and Chang 2013)—can contribute to low uptake of sustainable behaviors. Moreover, intelligence (Aspara, Luo, and Dhar 2017), education (Gifford and Nilsson 2014), and knowledge (Levine and Strube 2012) are linked to greater responsiveness to environmental appeals and engagement in eco-friendly behaviors. In many ways, knowledge is relevant across all our SHIFT factors.…”
Section: The Shift Frameworkmentioning
confidence: 99%
“…Some have lamented that people’s dearth of understanding and knowledge—due to lack of exposure to information (Gifford 2011), information overload (Horne 2009; Neumann, Roberts, and Cauvin 2012), and confusion (Chen and Chang 2013)—can contribute to low uptake of sustainable behaviors. Moreover, intelligence (Aspara, Luo, and Dhar 2017), education (Gifford and Nilsson 2014), and knowledge (Levine and Strube 2012) are linked to greater responsiveness to environmental appeals and engagement in eco-friendly behaviors. In many ways, knowledge is relevant across all our SHIFT factors.…”
Section: The Shift Frameworkmentioning
confidence: 99%
“…We also add to the literature that focuses on IQ and consumer decision making in real-world markets (Aspara et al, 2017;Aspara & Wittkowski, 2019;Grinblatt et al, 2016). Finally, our findings contribute to the literature investigating the role of numerical ability in decision making (Agarwal & Mazumder, 2013;Gerardi et al, 2013).…”
mentioning
confidence: 64%
“…Field studies suggest that IQ is linked with price-consciousness in various markets. High-IQ individuals pay lower management fees for their mutual fund holdings (Grinblatt et al, 2016), are more likely to take advantage of favorable tax treatment on some product classes when purchasing cars (Aspara et al, 2017), and manage consumer debt cost-efficiently (Agarwal & Mazumder, 2013). Since gambling operators levy a higher take-out rate on volatile gambling products (Eadington, 1999), complex gambling formats are more expensive than simple ones.…”
Section: Iq and Choice Of Betting Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, responsiveness to pro-environmental taxes depends on cognitive ability. This implies that intelligence is a relevant variable to study as a moderator to choices that are carbon neutral [49]. Also, previous analyses have revealed that the life satisfaction of citizens is unrelated to their energy use [11].…”
Section: Behavioural Aspects Of Sociotechnical Changementioning
confidence: 98%